EKSPLORASI ETNOMATEMATIKA PADA KAIN TENUN IKAT MASYARAKAT SIKKA - Imelda Herlince; Stefanus Notan Tupen; Stefania Baptis Seto (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2021)
This research aims to find out; mathematical concepts on Sikka ikat woven fabric; Geometric shapes contained in the equipment of making Sikka ikat woven fabric. The type of research used is qualitative research with an ethnographic approach. The results showed the existence of geometric shapes on the motif of Sikka ikat is woven fabric and its manufacturing tools. Geometric form found in Sikka ikat woven fabric motif is Korosang Manu Walu motif in the form of two intersecting lines; Ekon Leben's motif is circular; Medeng motif in the form of a ketupat; Motifs in a square, triangular, and ketupat shaped motifs; Motif in hexagon-shaped plapat; the motif of the butuk shaped in the form of a straight line; Welan motif in the shape of a triangle. the geometric form is found in the equipment of making Sikka ikat woven fabric that is keho tool to separate seeds with cotton) in the form of two parallel lines; wetir (a tool to tann cotton fibres) in the form of two parallel lines; Jata (tool for spinning cotton) in the form of a circle; Another (tool for deciphering threads) in the form of line segments; Seler (a tool for rolling threads into clumps) in the form of two intersecting lines; Plapan Pete (thread stretching tool) rectangular in shape; Unu Tana (earth pot for cooking dye) in the form of balls; Plapan Stylist Motif (a tool to decipher threads that have been coloured) in the form of a rectangle; Legun (where the thread roll) is tube-shaped; Tu'un (tool for weavers leaning on the feet when weaving) in the form of beams.